Representation of the linguistic and cultural concept “lie” in the French and Russian language picture of the world - Kasatkina O.A., Shatilova L.M., Borisova V.V., (Opción, 2019)
The aim of this article is to establish similarities and differences in the representation of the linguistic and cultural concept ―Lie‖ in the French and Russian language picture of the world. As a result of the research, the authors came to the following conclusions. A comparative analysis of the semantics of the lexemes representing the concept ―Lie‖ in the French and Russian languages showed more similarities than differences, which confirm the long-term relationship of these languages, as well as the similarity of linguistic pictures of the world and the culture of the people.